The Relationship between Pregnant Women's Level of Knowledge about Nutrition and Anemia Status during Pregnancy - Oklin Dawa; Cakrawati R Cakrawati R (International Journal of Health Sciences, 2026)
Anemia during pregnancy is a common health problem that May increase the risk of complications for both mothers and fetuses . One factor that May be associated with anemia is the mother's level of knowledge regarding nutritional requirements during pregnancy . Adequate nutritional knowledge is expected to encourage pregnant women to choose nutritious foods , fulfill iron and other nutrients requirements , and improve adherence to iron supplementation .This study aimed to determine the relationship between pregnant women's nutritional knowledge and anemia status during pregnancy .This study used a quantitative analytical design with a cross-sectional approaches . The study population consisted of pregnant women attending antenatal care at a healthcare facilities . A total of 60 respondents were selected using purposive sampling. Nutritional knowledge was assessed using a questionnaire , while anemia status was determined based on hemoglobin (Hb) levels recorded from laboratory examinations . Univariate analysis was conducted to describe respondents characteristics , knowledge levels , and anemia status. Bivariate analysis was performed using the Chi- Square test with a significance level of α = 0.05.Based on simulated data, 25 respondents (41.7%) had good knowledge , 20 respondents (33.3%) had moderate knowledge , and 15 respondents (25.0%) had poor knowledge . A total of 24 respondents (40.0%) were anemic , while 36 respondents (60.0%) were not anemic . The Chi- Square test indicated a significant relationship between pregnant women's nutritional knowledge and anemia status during pregnancy (p < 0.05).There was a relationship between pregnant women's nutritional knowledge and anemia status during pregnancy . Improving knowledge about adequate nutrition​ iron intake , and adherence to iron supplementation should be strengthened as part of efforts to prevent anemia among pregnant women . Keywords : Pregnant Women, Nutritional Knowledge, Anemia, Pregnancy, Iron